Moderate rest intervals are superior to short intervals for improving PAI-1 following exhaustive exercise in recreational weightlifters - Rossi, Fabricio Eduardo [UNESP]; Gerosa-Neto, Jose [UNESP]; Diniz, Tiego Aparecido; Freitas Junior, Ismael F. [UNESP]; Lira, Fabio Santos [UNESP]; Cholewa, Jason Michael (Korean Soc Exercise Rehabilitation, 2016)
This study investigated the influence of short and moderate recovery intervals on lipid profiles and plasminogen activator inhibitor-1 (PAI-1) following exhaustive strength exercise in recreational weightlifters. Seven subjects performed two conditions in a randomized order: short, 90% of one maximum repetition (1RM) and 30-sec rest allowed between sets; moderate, 90% of 1RM and 90-sec rest allowed between sets. Total cholesterol (Chol), high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), triacylglycerol (TAG), Chol/HDL-c ratio and PAI-1 concentrations were assessed at baseline, immediately postexercise, and 15- and 30-min postexercise (post-15 and post-30). The LDL-c concentrations decreased and HDL-c concentrations increased in both conditions but without significant differences (LDL-c: 30 sec: pre, 82.0 +/- 19.5 mg/dL, immediately, 73.9 +/- 16.4 mg/dL, 90 sec: pre, 75.9 +/- 30.8 mg/dL, immediately, 66.2 +/- 35.5 mg/dL, P=0.423; HDL-c: 30 sec: pre, 53.5 +/- 9.2 mg/dL, immediately, 61.4 +/- 11.4 mg/dL; 90 sec: pre, 55.8 +/- 11.1 mg/dL, immediately, 84.9 +/- 27.8, mg/dL; P=0.146). On the other hand, PAI-1 had a tendency to decrease only in the 90-sec condition (pre, 7,754.9 +/- 2,927.7 pg/mL; immediately, 5,313.1 +/- 4,637.4 pg/mL; P=0.085). There was a positive correlation between PAI-1 and Chol (30 sec: r=0.83, 90 sec: r=0.91; P<0.05), PAI-1 and fat-free mass in both conditions (30 sec post-15: r=0.79, post-30: r=081, P<0.05; 90 sec immediately: r=0.77, post-15: r=0.81; P<0.05), and PAI-1 and TAG only in 30 sec (r=0.87, P<0.05). Short and moderate intervals of recovery improve lipid profiles after heavy strength exercise but only 90 sec induced greater improved in PAI-1 concentration in recreational weightlifters.
Keywords: Strength exercise; Interval of recovery; Fibrinolysis